Using Video to Improve Pronunciation of The Second Years Students of FKI UIR Pekanbaru - Al Malikul Ikhwanda Putra (Universitas Jambi, Magister Program of English Education Department, 2018)
The purpose of the research is to find out the use of video to improve students’ pronunciation. The study employed a classroom action research. The participants of this study were 37 students. They were the second year students of FKIP (faculty of teacher training and education) in Islamic University Riau (UIR) Pekanbaru, Indonesia. This study was conducted in two cycles. Each cycle comprised four meetings. The data of this research were obtained through (1) observation sheets, (2) field notes, (3) interview, and (4) tests which consisted of consonants in detail, linking, and stress within target segments based on the phonetic symbols. The findings showed that the use of video in mastering pronunciation was able to improve students’ pronunciation. The study also revealed that the activities of using video enable students to enhance the quality of sound patterns they pronounce. In this case the researcher found that the key factors that enhance the quality of sound patterns were also influenced by familiar words, student’s basic needs and level. Hence, those factors should be considered in learning and teaching pronunciation. Moreover, the activity such as listening and imitating the way native speaker pronounces words and sentences as the lesson material can help students improve their pronunciation. The average class score of students’ pronunciation increased from 58.4 in the first cycle to 88.3 in the second cycle. Material, media, classroom activities, classroom management, teacher’s approach, and teacher’s strategy were also significantly essential for the improvement of students’ pronunciation.